Simultaneous Analysis of the Influence of Flipbook Media and Learning Motivation on Senior High School Students’ History Learning Outcomes - Abbas, Navil Alfarisi; Afwan, Bahtiar; Sumargono, Sumargono; Setiawan, Johan (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to analyze the influence of flipbook media and learning motivation on high school students’ history learning outcomes, both partially and simultaneously. The research was conducted at SMAN 13 Bandar Lampung using a quantitative approach and a verificative method. The subjects consisted of 38 tenth-grade students selected through purposive sampling. Data were collected through questionnaires, observations, and documentation, then analyzed using simple and multiple regression tests. The findings indicate that flipbook media significantly affects students’ learning motivation and history learning outcomes. Learning motivation was also shown to have a significant influence on students’ history learning outcomes. Simultaneous analysis reveals that flipbook media and learning motivation collectively contribute significantly to improving learning outcomes. These findings highlight the importance of integrating interactive digital media to enhance student engagement while reinforcing theoretical perspectives regarding the relationship among learning media, motivation, and learning achievement. This research contributes to the development of history education by presenting an innovative instructional strategy that teachers may adopt to enhance learning quality.